Evaluation of a vital staining protocol with 2, 3, 5-triphenyltetrazolium chloride for cancellous bone in a sheep model. (October 2017) - Schiffner, René; Bischoff, Sabine J.; Matziolis, Georg; Schmidt, Martin
Abstract: Decision making on the optimal surgical treatment of fractures often is hampered by the lack of a method for direct assessment of bone vitality. In various contexts, for example to determine the extents of cerebral insults or of myocardial infarctions in experimental studies, tetrazolium based staining procedures of vital cells are widely used. Here, we set out to test the applicability of tetrazolium based staining on bone samples. 8 brains and 26 femoral heads from sheep were used to prepare tissue slices, which were stained with 2, 3, 5-triphenyltetrazolium chloride (TTC) at various times (1 to 12 h) after explantation. Staining of tissue slices was quantified by densitometric image analysis. Spectrophotometry was used for quantification in cultured cells. TTC-staining of tissue slices indicated detectability of vital cells in slices from both tissues up to 4 h after explantation. Staining intensity at later time-points was indistinguishable from the staining of untreated samples or sodium azide treated (necrotic cells) controls. We provide experimental evidence that the choice of the optimal surgical approach for the treatment of fractures involving cancellous bone could be aided by a simple staining procedure for vital bone. However, the described procedure depends on the availability of bone specimens (slices). Therefore, search for an improved stain directly applicable to the bone surface is needed. Highlights: In our manuscript we describe a simple procedure which could allow an intraoperative decision whether the concerned bone appears vital or non-vital, and thus could aid in the choice of the optimal therapeutic approach.